Efficient Synthesis of Polysubstituted 1,5-Benzodiazepinone Dipeptide Mimetics via an Ugi-4CR-Ullmann Condensation Sequence - Van Den Hauwe, Robin; Elsocht, Mathias; Hollanders, Charlie; Ballet, Steven (Synlett, 2021)
An efficient three-step synthesis towards 3-amino-1,4-benzodiazepin-2-one derivatives is presented. The versatile Ugi-4-component reaction (Ugi-4CR) and Boc deprotection is followed by a ligand-free Ullmann condensation. This protocol allows the rapid construction of a diverse array of substituted 1,5-benzodiazepinones. Since Ugi-based products are typically limited by their ‘inert’ C-terminal amides, the use of a convertible (‘cleavable’) isocyanide was envisaged and resulted in building blocks that can be made SPPS compatible. To demonstrate the potential of this novel synthetic route, the design and preparation of novel phenylurea-1,5-benzodiazepin-4(5H)-one dipeptide mimetics with potential CCK2-antagonist properties is reported.
Keywords: 1,5-benzodiazepinone; Ugi multicomponent reaction; Cu-catalyzed Ullmann cyclization; constrained dipeptides.